2020
DOI: 10.1099/ijsem.0.004444
|View full text |Cite
|
Sign up to set email alerts
|

Antrihabitans stalactiti gen. nov., sp. nov., a new member of the family Nocardiaceae isolated from a cave

Abstract: Two Gram-stain-positive, strictly aerobic, non-spore-forming actinobacterial strains, designated YC2-7T and YC5-17, were isolated from the Yongcheondonggul (larva cave) in Jeju, Republic of Korea and their taxonomic ranks were examined by a polyphasic approach. The 16S rRNA gene tree showed that the novel isolates occupied an independent position separated from recognized genera of the family Nocardiaceae . In the 92 core ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Proteobacteria, Fusobacteria, Firmicutes, Bacteroidetes, Actinobacteria and Clostridia (Villasante et al, 2019;Wong et al, 2013). In this study, and cellulose (Lee et al, 2020). Meanwhile, Actinobacteriota belongs to conditional pathogenic bacteria, which can infect the body and cause disease when the body's immunity is weak (Byrd et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…Proteobacteria, Fusobacteria, Firmicutes, Bacteroidetes, Actinobacteria and Clostridia (Villasante et al, 2019;Wong et al, 2013). In this study, and cellulose (Lee et al, 2020). Meanwhile, Actinobacteriota belongs to conditional pathogenic bacteria, which can infect the body and cause disease when the body's immunity is weak (Byrd et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…For sequencing of 16S rRNA genes, the 10 study strains were grown on marine agar at 30 • C for 3 days, and Microbacterium arthrosphaerae KACC 16680 T , M. luteolum KACC 14465 T , and Microbacterium terrae KACC 14470 T were cultivated on trypticase soy agar (Difco) at 30 • C for 3 days. Genomic DNA isolation was performed as described previously (Lee et al, 2020). The PCR amplification and sequencing of the 16S rRNA genes were performed using an ABI Prism 3730XL DNA analyzer with a BigDye Terminator kit v.3.1 (Invitrogen, USA) at the SolGent Company Limited (Deajon, Korea).…”
Section: S Rrna Gene Sequencing and Analysismentioning
confidence: 99%
“…Caves represent an interesting environment that is unique and distinct from other terrestrial habitats. During a screening for novel actinobacteria from a natural cave in Jeju Island, Republic of Korea, many novel bacterial strains that were affiliated to the class Actinobacteria were described [9,[11][12][13][14][15]. Among them, it was found that two actinobacterial strains, designated as D2-41 T and D3-21, showed an uncertain taxonomic rank within the order Mycobacteriales through preliminary 16S rRNA gene sequence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the eight families, except for the families Hoyosellaceae and Lawsonellaceae, are known to contain mycolic acids [1,8], unique long-chain fatty acids (with 22-90 carbon atoms) found in the lipid-rich cell walls. Recently, three mycolic acid-containing genera, namely Antrihabitans [9], Presttcolla [10] and Sphaelaeibacter [11], were proposed as new members of the family Nocardiaceae.…”
Section: Introductionmentioning
confidence: 99%